Increasing the H2 production rate of ZnS(en)x hybrid and ZnS film by photoexfoliation process. (26th June 2022) - Cerezo, Lorena; Valencia G., Karen; Hernández-Gordillo, Agileo; Bizarro, Monserrat; Acevedo-Peña, Próspero; Rodil, Sandra E.
Abstract: Zinc sulfide nanosheets with different ethylenediamine contents (ZnS(en)0.5 and ZnS(en)0.25 hybrids) were prepared by solvothermal and hydrothermal methods at 100 °C and were sequentially sonicated-irradiated during 24 and 48 h to induce a photoexfoliation process. The influence of the photoexfoliation in the physicochemical properties and stability of both ZnS(en)0.5 and ZnS(en)0.25 hybrid nanosheets was investigated by diverse techniques: X-ray Diffraction, Textural analysis, Infrared, Diffuse Reflectance, and Scanning Electron Microscopy. Then, the as-prepared and exfoliated hybrid nanosheets were deposited on glass substrates using spin coating. The photocatalytic H2 production of the films was evaluated using an ethanol-water mixture for 6 h and three reaction cycles. A significant increase in the amount of produced H2 was obtained for the exfoliated solvothermal sample, results that were correlated with the photoelectrochemical characterization of the films. Graphical abstract: Image 1 Highlights: ZnS(en)0.5 hybrid was prepared by solvothermal and hydrothermal route. Sheets of ZnS(en)0.5 and ZnS(en)0.25 hybrid were obtained. Lamellar exfoliation was achieved by sonication/irradiation process. Thin films of each material were deposited on glass substrates by spin coating technique. High H2 evolution rate was achieved with exfoliated ZnS(en)0.5 film.